Effects of Revision Rod Position on Spinal Construct Stability in Lumbar Revision Surgery: A Finite Element Study - Tan, Quan-Chang; Huang, Jin-Feng; Bai, Hao; Liu, Zi-Xuan; Huang, Xin-Yi; Zhao, Xiong; Yang, Zhao; Du, Cheng-Fei; Lei, Wei; Wu, Zi-Xiang (Frontiers in Bioengineering and Biotechnology, 2022)
Revision surgery (RS) is a necessary surgical intervention in clinical practice to treat spinal instrumentation–related symptomatic complications. Three constructs with different configurations have been applied in RS. One distinguishing characteristic of these configurations is that the revision rods connecting previous segments and revision segments are placed alongside, outside, or inside the previous rods at the level of facetectomy. Whether the position of the revision rod could generate mechanical disparities in revision constructs is unknown. The objective of this study was to assess the influence of the revision rod position on the construct after RS. A validated spinal finite element (FE) model was developed to simulate RS after previous instrumented fusion using a modified dual-rod construct (DRCm), satellite-rod construct (SRC), and cortical bone trajectory construct (CBTC). Thereafter, maximum von Mises stress (VMS) on the annulus fibrosus and cages and the ligament force of the interspinous ligament, supraspinous ligament, and ligamentum flavum under a pure moment load and a follower load in six directions were applied to assess the influence of the revision rod position on the revision construct. An approximately identical overall reducing tendency of VMS was observed among the three constructs. The changing tendency of the maximum VMS on the cages placed at L4-L5 was nearly equal among the three constructs. However, the changing tendency of the maximum VMS on the cage placed at L2-L3 was notable, especially in the CBTC under right bending and left axial rotation. The overall changing tendency of the ligament force in the DRCm, SRC, and CBTC was also approximately equal, while the ligament force of the CBTC was found to be significantly greater than that of the DRCm and SRC at L1-L2. The results indicated that the stiffness associated with the CBTC might be lower than that associated with the DRCm and SRC in RS. The results of the present study indicated that the DRCm, SRC, and CBTC could provide sufficient stabilization in RS. The CBTC was a less rigid construct. Rather than the revision rod position, the method of constructing spinal instrumentation played a role in influencing the biomechanics of revision.